The impact of corporate governance on the voluntary accounting information disclosure in Malaysian listed banks - Htay, Sheila Nu Nu; Abdul Rashid, Hafiz Majdi; Adnan, Muhammad Akhyar; Mydin Meera, Ahamed Kameel (2011)
Financial accounting information is the main part of the annual reports on which investors rely on. The reliability and relevant of the financial accounting information is on the shoulders of directors. It has been highlighted in the corporate governance literature that information disclosure about the companies is the heart of the good corporate governance system. In Malaysia, there is no research conducted to examine the relationship between corporate governance and voluntary accounting information disclosure although it is important to examine on it. Therefore, the objective of this research is to investigate the impact of corporate governance on voluntary financial accounting information disclosure of Malaysian listed banks. The findings of the panel data regression show that higher INE_BZ (at 1% Sig. level), lower DOWN (at 10% Sig. level) and higher BZ (at 5% Sig. level) have more voluntary financial accounting information disclosure. The other variables such as BLS, IOWN and BOWN in line with hypothesis while BZ is not in and the main reason for BZ not being in line with hypothesis is the sample firms already have optimal board.